Policy for rapid growth in use of modern agricultural inputs - Desai, Gunvant M. (International Food Policy Research Institute, 1988)
Accelerated growth in agricultural production of developing countries depends on exploiting more fully the existing production potential and continuously raising that potential through technological change. This requires sustained rapid growth in the use of inputs such as seeds of better quality, fertilizers, pesticides, farm implements, and machinery. Price policy issues dominate in discussions on how to increase the use of these inputs, often without sufficient attention to certain non-price factors and policies. Such an approach is lopsided and could mislead us as to the role and limitations of price policy in the use of modern agricultural inputs in developing countries.